Pengaruh Kepemimpinan, Kompensasi, dan Lingkungan Kerja terhadap Kinerja Karyawan - Pehteng Juventus Basso (Indonesian Maritime Researchers and Lecturers, 2025)
This research aims to analyze the partial and simultaneous influence of Leadership (X₁), Work Motivation (X₂), Compensation (X₃), and Work Environment (X₄) on Employee Performance (Y) at PT. Kalisari Putra Semarang, a company in the transportation sector. Using a quantitative associative method, data were collected from a census of 85 permanent employees (N=85) through questionnaires and analyzed using multiple linear regression (SPSS). The results confirmed that all four independent variables significantly and positively influence employee performance (all tₕᵢᵗᵘⁿg > tₜₐᵦᵉᵡ 1.66). Leadership (X₁) was found to be the most dominant factor, with the highest regression coefficient (β = 0.373), followed by Compensation (β = 0.182), Work Environment (β = 0.145), and Work Motivation (β = 0.110). The model demonstrated a strong explanatory power, with the Coefficient of Determination (R²) reaching 0.898, indicating that 89.80% of the variation in employee performance is explained by these factors. The main managerial implication is that improving leadership quality and competency is the most critical factor for maximizing employee performance in this company.